2020
DOI: 10.1177/2058739220960558
|View full text |Cite
|
Sign up to set email alerts
|

Study of three novel biomarkers, MR-proADM, midkine, and stromelysin2, and peripheral atherosclerosis in a Chinese Han population: A case-control study

Abstract: Midregional pro-adrenomedullin (MR-proADM), midkine, and stromelysin2 (ST2) are novel cardiac biomarkers associated with heart failure and atherosclerotic diseases like stable ischemic disease and acute coronary syndrome. The potential association between these three biomarkers and peripheral artery disease (PAD) remains unclear. The aim of this study was to assess the correlation between these three biomarkers and their association with PAD in the Chinese Han population. This study included 224 patients suspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…In mice, knockout of Dkk3 leads to greater infarcts and aggravated left ventricular function [ 46 ]. ADM, a vasoactive peptide, is involved in some cardiovascular pathophysiological processes, including vasodilatation and modulation of vascular calcification [ 47 ]. In patients with cardiovascular diseases, ADM is significantly up-regulated in the epicardial adipose tissue [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…In mice, knockout of Dkk3 leads to greater infarcts and aggravated left ventricular function [ 46 ]. ADM, a vasoactive peptide, is involved in some cardiovascular pathophysiological processes, including vasodilatation and modulation of vascular calcification [ 47 ]. In patients with cardiovascular diseases, ADM is significantly up-regulated in the epicardial adipose tissue [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Guzel et al demonstrated that MK serum levels correlate positively with hypertension and lipid profile [39]. Besides MK, clinical studies have also revealed other biomarkers associated with CVD, such as heart failure and atherosclerosis such as midregional pro-adrenomedullin or stromelysin2 studied in isolation or associated with MK [58].…”
Section: Midkine-a Biomarker For All Stages Of Atherosclerosismentioning
confidence: 99%
“…Adrenomedullin (ADM) is a vasoactive peptide involved in multiple cardiovascular pathophysiological processes such as vasodilatation, natriuresis, increasing cardiac output, or modulation of vascular calcification [58]. Moreover, ADM inhibits VSMC proliferation and neoangiogenesis and promotes the re-epithelialization process [221].…”
Section: Biomarkers Of Thrombocyte Activation-midregional Proadrenome...mentioning
confidence: 99%